Sexual dimorphism in the association of umbilical cord blood lipidome with abdominal fat in early childhood - Kothandaraman Narasimhan; Mya Thway Tint; Li Chen; Sartaj Ahmad Mir; Suresh Anand Sadananthan; Navin Michael; Adaikalavan Ramasamy; Karen Mei-Ling Tan; Priti Mishra; Anne K. Bendt; Kok Hian Tan; David Cameron-Smith; et al. (BMC Medicine)
Abstract Background Although the associations between cord blood lipidome and neonatal birth weight are established, it remains uncertain whether sexual dimorphism in fetal fat accumulation extends to the relationship between cord blood lipid profiles and neonatal abdominal fat compartments. Understanding these relationships could provide insights into early sex-specific differences in lipid metabolism. Methods We conducted lipidomics of umbilical cord blood plasma samples (350 (46.6%) girls and 401 (53.4%) boys) from the Growing Up in Singapore Towards healthy Outcomes (GUSTO) birth cohort. Abdominal fat compartments—superficial subcutaneous adipose tissue (sSAT), deep SAT (dSAT), and intra-abdominal adipose tissue (IAT)—were quantified by magnetic resonance imaging within 2 weeks of birth in 239 subjects. Linear regression models were used to assess sex differences in lipid species associated with abdominal fat compartments. Results Newborn girls had significantly higher superficial and deep subcutaneous adipose tissue volumes compared to boys, whereas intra-abdominal adipose tissue volumes were similar between sexes. In the pooled analysis, cord blood plasma lipids showed distinct associations with different fat depots: 38 lipid species were associated with sSAT, 4 with dSAT, and 38 with IAT. In sex-stratified analyses, 13 lipids were associated with sSAT in girls and 3 in boys, whereas dSAT showed associations with 45 lipids in boys but none in girls. These sex differences were primarily observed in ether-linked phospholipids and ceramides. Notably, no significant associations were observed between lipids and IAT in either sex, suggesting depot-specific sexual dimorphism in early life. Conclusions Our study reveals sexual dimorphism in the associations between cord blood lipidome and abdominal adiposity, suggesting depot-specific patterns in adipose tissue development and lipid metabolism in early life.